2007
DOI: 10.1243/09544054jem693
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of three processes for producing castings incorporating micro/mesoscale features with a high aspect ratio

Abstract: This paper investigates the capabilities of three different process chains for vacuum investment casting of parts incorporating micro/mesoscale features. The first two process chains employ the classical Lost Wax Process and make use of layer-based manufacturing technologies, ThermoJet and PatternMaster respectively, to create patterns out of a thermoplastic material, while the third one, Fcubic, produces directly a casting tree in zirconia ceramics. The study involves the manufacture of test parts in aluminiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Wu et al [60], Everton et al [61], and Fayazfar et al [62] conducted reviews of the use of stainless steel powder as the feedstock material in AM. Charmeux et al [63] investigated the performance of three process chains for vacuum investment casting of aluminum/zinc alloys and stainless steel parts. The property parameters considered were dimensional accuracy, surface quality, and production costs of the three process chains.…”
Section: Stainless Steel-based Alloysmentioning
confidence: 99%
“…Wu et al [60], Everton et al [61], and Fayazfar et al [62] conducted reviews of the use of stainless steel powder as the feedstock material in AM. Charmeux et al [63] investigated the performance of three process chains for vacuum investment casting of aluminum/zinc alloys and stainless steel parts. The property parameters considered were dimensional accuracy, surface quality, and production costs of the three process chains.…”
Section: Stainless Steel-based Alloysmentioning
confidence: 99%
“…95 It was reported that a conventional vacuum casting process with minor changes can be employed to fabricate microstructures, high AR structures and submicrometer features. 96 Microprecision investment casting is adapted to parts smaller than 1 mm and to bigger ones with structural details in micrometer range (Figure 10). 85 It was shown that features with size less than 150 μm, ribs with AR higher than 50 and surface roughness around 5 μm could be reproduced with an accuracy of 10% or less.…”
Section: Microcastingmentioning
confidence: 99%
“…89 The capabilities of two different process chains, lost-wax process and direct shell process, for producing accurate castings having micro/mesoscale features have been compared. 96 The soundness, quality, microstructure and production cost of castings manufactured by employing these two processes are also discussed in detail.…”
Section: Microcastingmentioning
confidence: 99%
“…Several analyses have been conducted to examine the molding accuracy of this process. The casting accuracy of microparts using aluminum/zinc alloys [5,6] and stainless steel [7] as well as low melting Au-Ag-based precious metal alloys was investigated [8]. According to these results, microparts with geometrical features in a range of 700-50 μm can be cast with acceptable geometrical variation and an average surface roughness between 0.5 and 1 μm.…”
Section: Introductionmentioning
confidence: 99%